The Benefit of Shift Work Schedules for Nurses’ Outcome: A Sytematic Review - Mahmud Ady Yuwanto (Poltekkes Kemenkes Semarang, 2022)
Background: the nurse scheduling problem (NSP) is a serious and complex challenge in the medical industry. Effective, efficient, and high-quality services must be carried out by nurses in hospitals.Purpose: the goal of the systematic review was to find out how nurses have a positive impact on shift schedules on professional nurses in hospitals.Methods: employed the PRISMA approach. Electronic search engines from Proquest, Science Direct, and Ebsco were used to locate pertinent publications. Only English-language publications released between January 1, 2019 and December 31, 2021, had an inpatient hospital focus.Results: after identifying 265 references initially, duplicates were eliminated, and then authors from 6 pertinent papers were chosen. Overall, nurses reported that 12-hour shifts had a favorable impact on retention, including